Co‐expression of HSV‐1 ICP34.5 enhances the expression of gene delivered by self‐amplifying RNA and mitigates its immunogenicity - Xuemin Lu; Yabin Wu; Chunye Zhao; Jie Zheng; Shangwu Chen; Yigang Wang; Yulong Xia (FEBS Open Bio, 2025)
Self‐amplifying RNA (saRNA) vectors have garnered significant attention for their potential in transient recombinant protein expression and vaccination strategies. These vectors are notable for their safety and the ability to produce high levels of protein from minimal input templates, offering a promising avenue for gene therapy applications. Despite their advantages, saRNA vectors face a critical challenge in their propensity to trigger a robust innate immune response. The presence of double‐stranded RNA intermediates during saRNA replication activates pattern recognition receptors (PRRs), leading to the activation of protein kinase R (PKR) and interferon (IFN) signaling, which can result in a general translational shutdown within the host cell. To mitigate the stimulatory effects on PRRs and enhance the translation efficiency of saRNA, this study employs the saRNA‐encoding HSV‐1 neurovirulence protein ICP34.5, which is known for its ability to counteract the effects of PKR activation, potentially improving the translation efficiency of saRNA. It was shown that saRNA‐encoding ICP34.5 clearly mediated the eukaryotic initiation factor 2 alpha subunit (eIF2α) dephosphorylation and significant suppression of innate immune responses in vitro, leading to enhanced expression of saRNA‐encoded genes. The application of ICP34.5 incorporating saRNA vectors offers a more efficient and cost‐effective solution for the production of proteins and the development of vaccines. This strategy could revolutionize the fields where saRNA utilization is envisioned, particularly in neurotropic disease applications where HSV‐1 proteins may offer additional benefits.